Digital Interventions for Generalized Anxiety Disorder (GAD): Systematic Review and Network Meta-Analysis - Saramago, Pedro; Gega, Lina; Marshall, David; Nikolaidis, Georgios F.; Jankovic, Dina; Melton, Hollie; Dawson, Sarah; Churchill, Rachel; Bojke, Laura (Frontiers in Psychiatry, 2021)
Background: Generalised anxiety disorder is the most common mental health condition based on weekly prevalence. Digital interventions have been used as alternatives or as supplements to conventional therapies to improve access, patient choice and clinical outcomes. Little is known about their comparative effectiveness for generalised anxiety disorder. Methods: We conducted a systematic review and network meta-analysis of randomised controlled trials comparing digital interventions with medication, non-digital interventions, non-therapeutic controls and no intervention. Results: We included 21 randomised controlled trials with a total of 2,350 participants from generalised anxiety disorder populations. Pooled outcomes using analysis of Covariance and rankograms based on the surface under the cumulative ranking curves indicated that antidepressant medication and group therapy had a higher probability than digital interventions of being the ‘best’ intervention. Supported digital interventions were not necessarily “better” than unsupported (pure self-help) ones. Conclusions: Due to very wide confidence intervals, network meta-analysis results were inconclusive as to whether digital interventions are better than no intervention and non-therapeutic active controls, or whether they confer an additional benefit to standard therapy. Future research needs to compare digital interventions with one-to-one therapy and with manualised non-digital self-help and to include antidepressant medication as a treatment comparator and effect modifier.